2021
DOI: 10.3390/ijerph18126540
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Shift Work and Long Working Hours on Worker Cognitive Functions: Current Evidence and Future Research Needs

Abstract: Particular working conditions and/or organization of working time may cause important sleep disturbances that have been proposed to be predictive of cognitive decline. In this regard, circadian rhythm misalignment induced by exposure to night work or long working hours would be responsible for cognitive impairment. Nevertheless, evidence supporting this correlation is limited and several issues still need to be elucidated. In this regard, we conducted a systematic review to evaluate the association between shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 78 publications
2
23
0
Order By: Relevance
“…The nurses suffer from insufficient sleep and extreme fatigue for long working hours that exceed the recommended limit, which is at least 7 hours of sleep. This result reflects the health institution's policy, requirements and work schedules that require night work to deliver health service within 24 hours, and this finding is consistent with the Italian study(Leso et al 2021). Table4-3 indicates that the nurses have experienced moderately insufficient sleep to completely insufficient sleep, respectively, and this result is related to the work system in the night shifts of the intensive care units.…”
supporting
confidence: 84%
“…The nurses suffer from insufficient sleep and extreme fatigue for long working hours that exceed the recommended limit, which is at least 7 hours of sleep. This result reflects the health institution's policy, requirements and work schedules that require night work to deliver health service within 24 hours, and this finding is consistent with the Italian study(Leso et al 2021). Table4-3 indicates that the nurses have experienced moderately insufficient sleep to completely insufficient sleep, respectively, and this result is related to the work system in the night shifts of the intensive care units.…”
supporting
confidence: 84%
“…In a systematic analysis carried out jointly by the World Health Organization (WHO) and the International Labor Organization (ILO), individuals who work long hours have a higher risk of developing ischemic heart disease and stroke [ 50 ]. Other systematic reviews have also revealed that long working hours are associated with burnout syndrome [ 51 ], decline cognitive capacity [ 52 ], depression [ 53 , 54 ], increased alcohol consumption [ 55 ], mental health disorders [ 56 ], and adverse pregnancy outcomes (preterm birth, chance of miscarriage, low birth weight) [ 57 ]. High work demands related to working hours and shift and night-work are also associated with problems such as burnout and anxiety [ 58 ], musculoskeletal disorders [ 59 ], sleep disorders [ 60 ], emotional exhaustion [ 61 ], and sedentary lifestyle [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of SW on cognition are well-documented in studies of shift workers, both within nursing and outside of nursing. Anesthesia residents, emergency physicians, and miners who engaged in the night shift demonstrated a greater deterioration in cognitive functions compared to day shift workers ( Saricaoğlu et al, 2005 ; Machi et al, 2012 ; Leso et al, 2021b ). The laboratory setting and Aβ-PET evaluation confirmed the increase of Aβ after sleep deprivation ( Ooms et al, 2014 ; Shokri-Kojori et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%